Evidence-based recommendations for diagnosing and managing dentine hypersensitivity in clinical practice: insights from the Middle East and Africa - Cekici, Ali; Shaikh, Amynah; Alsayed, Arwa; Gokbuget, Aslan Yasar; Patel, Ebrahim; Marei, Hesham; Awad, Manal; Banday, Ninette; Habib, Nour A.; Osailan, Samira M.; Theuri, Tim; Adeyemi, Tope Emmanuel; et al. (Frontiers in Oral Health, 2025)
Dentine hypersensitivity (DH) is a common yet often overlooked oral condition that causes pain and discomfort, negatively impacting quality of life. The prevalence of DH in the Middle East and Africa (MEA) region is relatively higher than in European countries, highlighting the need for interventions to reduce the disease burden associated with DH. A systematic approach and a thorough understanding of the condition are required for proper diagnosis and management. However, the lack of specific treatment guidelines in the MEA region poses a challenge for clinicians in identifying and managing DH. To address this, an advisory board panel of 12 dental experts from 8 MEA countries developed these consensus recommendations for DH diagnosis and management. This paper presents an overview of the clinical presentation, diagnostic challenges, and management strategies specific to the MEA region. It provides evidence-based recommendations and a simplified algorithm to guide clinicians in diagnosing and managing DH effectively. The panel underscored the importance of early diagnosis, preventive education, behavioral modification, and personalized treatment interventions, including self-care home-based therapies, for optimal DH management. Additionally, the panel emphasized the need for heightened public awareness and the integration of DH education into dental professional curricula.